To redistribute or not to redistribute? The effects of inequality, development, absolute and relative income, and party polarisation on preferences for redistribution - Pastor Mayo, M (2023)
When do people want redistribution? Income inequality has been on the rise in recent decades, especially in advanced democracies. Since redistribution is the main tool that governments have at their disposal to ameliorate income disparities, and government policies are (at least partly) influenced by public opinion, abating income inequality will largely depend on whether people want redistribution. Therefore, this has brought renewed importance to understanding the determinants of support for redistribution.